P874 Comparison and Propensity Score of Seroconversion After Two Doses Of SARS-CoV-2 Vaccine in IBD Patients And Liver Transplant Recipients. (30th January 2023) - Indellicati, G; Rendina, M; Todeschini, A; Lillo, C; Castellaneta, A; D'Uggento, A M; Di Leo, A; Principi, M
Abstract: Background: Suboptimal anti-Sars-Cov2 vaccine response has been demonstrated during immunosuppressive treatments. Liver Transplant Recipients (LTRs) and Inflammatory Bowel Disease (IBD) patients are different setting of populations who are both undergoing immunosuppressive treatments. In this work, we pooled and compared, retrospectively, these two populations to evaluate anti-SARS-CoV2 seroconversion after the second dose of vaccination. Different comorbidities and therapies outcomes have been explored as well. Methods: The antibody titres standardized of the two cohorts have been analysed. Matched patients of both populations for comorbidities and therapies with application of propensity score have been investigated. Results: 240 LTRs and 424 IBD patients were analysed. Most have received an mRNA based vaccine (BNT162b2 or mRNA-1273: 99.1%). The seroconversion rate of 84% for LTRs and 93% for IBD patients was recorded. To multivariate analysis, hypertension (OR 2.8618, 95% CI 1.0012 to 8.1802), the mycophenolate administration (OR 2.9733, 95% CI 1.1820 to 7.4794) and the steroid use (OR 5.4531, 95% CI 1.0706 to 27.7761) were significantly associated with reduced seroconversion in LTRs cohort; meanwhile, the older age (OR 1.0369, 95% CI 1.0076 to 1.0670) and the thiopurine consumption (OR 2.9484, 95% CI 1.0089 to 8.6166) with that in IBD population. After Propensity Score Matching application, the seroconversion rates, not statistically different, of 86% for LTRs and 92% for IBD patients were found. Hypertension (OR 2.73, 95%CI 1.1258 to 6.6138), diabetes (OR 3.16, 95% CI 1.1888 to 8.4217), age > 65y (OR 2.93, 95% CI 1.1712 to 7.3153) and the female sex (OR 2.54, 95% CI 1.0963 to 5.9104) were correlated with reduced seroconversion in both populations. Conclusion: After Propensity Score Matching, the seroconversion rates of IBD and LTR patients were not statistically different. Hypertension, diabetes and age > 65y revealed a significant influence on seroconversion and the female showed a reduced seroconversion in comparison to male.